Chest X-Ray in Coronavirus Disease 2019 (COVID-19) Infection: Findings and Correlation with Clinical Outcome at Level-3 Nepalgunj Medical College and Teaching Hospital Kohalpur - BK, Shyam Kumar; Pandey, Sumit; Poudel, Nabin; Pandit, Sandesh; Sah, Alok Kumar; Neupane, Hitesh (Journal of Nepalgunj Medical College, 2020)
Introduction: At the end of 2019 a novel virus, named SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2), expanded globally from China. A new coronavirus, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), was identified as the cause of this outbreak of viral pneumonia that causes coronavirus disease 2019 (COVID-19). Aims: The aim of this study is to find out the chest radiological features of corona virus disease patients and correlate them with clinical outcome. Methods: This is a Hospital based study involving patients with clinical-epidemiological aspect of all reverse transcription polymerase chain reaction (RT-PCR) corona virus disease (COVID-19) positive patients, who performed Chest X-Rays at the emergency department of Nepalgunj Medical College, Teaching Hospital from March to June, 2020. All patients performed reverse transcription polymerase chain reaction from nasopharyngeal and throat swab, Chest X-Ray at the Emergency Department and clinical-epidemiological data. Results: Patients with a reverse transcription polymerase chain reaction positive results for corona virus disease infection were 32 out of these, 22 were females (68.75%) and 10 males (31.25%), with a mean age of 40.78 years (range 20–74 years). Only 2 Chest X-Rays were negative for radiological thoracic involvement (6.25%). The following alterations were more commonly observed among 30 patients: 18 patients with lung consolidations (56.25%), 19 (59.37%) with Ground Glass Opacities, 7 (21.87%) with nodules and 21 (65.6%) with reticular–nodular opacities. Patients with consolidations and Ground Glass Opacities coexisting in the same radiography were 34.37% of total. In reverse transcription polymerase chain reaction positive patients, we found also signs nonspecific for corona virus disease pneumonia as hilar or vascular congestion (37.5%), cardiomegaly (28.12%), pleural effusion (15.6%) and pneumothorax (3.12%). Peripheral (56.25%) and lower zone distribution (56.25%) were the most common predominance. Bilateral involvement (68.75%) was most frequent than unilateral one. Given the results, baseline Chest X-Rays sensitivity in our experience is about 65.62%. Conclusion: In this study, COVID-19 CXRs generally manifested a spectrum of pure ground glass, mixed ground glass opacities to consolidation in bilateral peripheral middle and lower lung zones. BSTI CXR reporting classification of COVID-19 is valid and sensitive in our patients with addition of middle zonal involvement in classical COVID-19 criteria as opposed to just lower zone involvement.